2020
DOI: 10.1002/rcs.2113
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the true benefit of robotic surgery: Ergonomics

Abstract: BackgroundErgonomics, as defined by the optimization of one's physical environment to enhance work performance, is an important consideration in surgery. While there have been reviews on the ergonomics of laparoscopy, this has not been the case for robotic surgery despite the rising number of publications.MethodsThis study was performed in accordance to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines. A search was performed on main databases to identify relevant artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 44 publications
3
64
0
4
Order By: Relevance
“…Despite the disadvantages of longer operative times and higher cost, the robotic surgical system has some advantages, such as enlarged three-dimensional views, allowing flexibility of wrist movement, and filtering hand tremors, which allow surgeons to perform meticulous operations in a small space and make it convenient to deal with intraoperative emergencies such as bleeding. Besides, some studies have shown that robots conferred superior ergonomic benefits and reduced workloads for surgeons when compared to laparoscopy as well as can possibly optimize surgeon performance by reducing fatigue [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the disadvantages of longer operative times and higher cost, the robotic surgical system has some advantages, such as enlarged three-dimensional views, allowing flexibility of wrist movement, and filtering hand tremors, which allow surgeons to perform meticulous operations in a small space and make it convenient to deal with intraoperative emergencies such as bleeding. Besides, some studies have shown that robots conferred superior ergonomic benefits and reduced workloads for surgeons when compared to laparoscopy as well as can possibly optimize surgeon performance by reducing fatigue [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The operative workflow is delivered through mechatronically enhanced robotic Endo Wrists ® , which provide enhanced articulation beyond the limits of human wrist movements and eliminates human hand tremors, thus facilitating superior operative dexterity with augmented precision for surgical dissection while preserving stable tissue retraction ( Figure 1 ). The surgeon adopts a sitting posture in the robotic console, with adjustable settings of the viewer’s height and tilt, arm rest height, and the position of the pedal platform, collectively designed and demonstrated to improve the ergonomics of the operating surgeon when compared to laparoscopic surgery [ 17 ]. It is worth noting that similar feasibility studies demonstrating the safety and the potential advantages of robotic-assisted pelvic exenteration have also been reported in other tumour groups, such as recurrent endometrial and cervical cancers.…”
Section: Robotics In Pelvic Exenteration Surgerymentioning
confidence: 99%
“…The robotic-assisted ASFC did not present any advantage over the laparoscopic-assisted ASFC; however, it did provide surgeons with a better ergonomic experience (16). Catanzarite et al (17) reviewed the ergonomics of surgery, and found that work-related musculoskeletal disorders are common among surgeons, with rates of 66-94% for open surgery, 73-100% for conventional laparoscopy, 54-87% for vaginal surgery, and 23-80% for robotic-assisted surgery (17).…”
Section: Discussionmentioning
confidence: 85%